Dampak Pola Asuh Keluarga Cerai Pada Perkembangan Anak Usia Dini - Widya Nurkayatin; Miftakhul Jannah; Yes Matheus Lasarus Malaikosa (Jurnal Mahasiswa Kreatif, 2024)
Parental divorce significantly impacts early childhood development, especially in the digital age. Children may experience low self-esteem, difficulties in building relationships and socializing, aggressive behavior, learning difficulties, value confusion, deviant behavior, and loss of trust.Addressing these impacts requires digital parenting, open communication, moral education, and collaboration with educational institutions. Parents and stakeholders must understand the effects of divorce to provide appropriate support for children's healthy and happy growth. A qualitative case study at TK Negeri Bung Karno involved interviews with PAUD teachers and parents, as well as classroom observations. The findings showed that children tend to imitate negative parental behaviors. Through gradual guidance, children learned to distinguish between good and bad behavior, showing progress in emotional control, social interactions, and setting positive examples for peers.